Biomechanical testing of a polycarbonate-urethane-based dynamic instrumentation system under physiological conditions. (January 2019) - Beckmann, Agnes; Herren, Christian; Nicolini, Luis Fernando; Grevenstein, David; Oikonomidis, Stavros; Kobbe, Philipp; Hildebrand, Frank; Stoffel, Marcus; Markert, Bernd; Siewe, Jan
Abstract: Background: Posterior dynamic stabilization systems are developed to maintain the healthy biomechanics of the spine while providing stabilization. Numerous dynamic systems incorporate polycarbonate urethane with temperature- and moisture-dependent material properties. In the underlying study, a novel test rig is used to evaluate the biomechanical performance of a system containing polycarbonate urethane. Methods: The test rig is composed of two hydraulic actuators. An environmental chamber, filled with water vapor at body temperature, is included in the set up. The translational and rotational degrees of freedom of vertebrae and pedicle screws are measured using a magnetic tracking system. The Transition® device is tested in five lumbar spines (L2–L5) of human cadavers. Pure moment tests are performed for flexion-extension, lateral bending, and axial rotation. Three test conditions are compared: 1. native specimens, 2. dynamic instrumentation at L4–L5, 3. dynamic instrumentation with decompression at L4–L5. Findings: The ranges of motion, the centers of rotation, and the pedicle screw loosening are calculated and evaluated. During daily motions such as walking, the loads on the lumbar spine differ from the standardized test protocols. To allow a reproducible data evaluation for smaller deformations, all moment-rotation curves are parameterized using sigmoid functions. Interpretation: In flexion-extension, the Transition® device provides the highest stiffening of the segment and the largest shift of the center of rotation. No shift in the center of rotation, and the smallest supporting effect on the segment is observed for axial rotation. In lateral bending, a mediate reduction of the range of motion is observed. Highlights: Spine test rig with environmental chamber to assess the kinematics of multiple spinal segments Significant reduction of the range of motion after instrumentation for all loading directions The centre of rotation was shifted after instrumentation The area and initial stiffness of the range of motion curves increase after instrumentation